2011
DOI: 10.1021/bm200616v
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor: Layered Silicate Nanocomposites for Tissue Regeneration

Abstract: Wound healing is a complex, multistep process that can be summarized into three stages, namely, hemostasis and inflammation, proliferation, and finally, tissue remodeling. Battlefield wound healing demands rapid hemostasis using clotting or cauterizing agents to immediately limit blood loss, but this occurs at the expense of proper tissue repair beyond hemostasis. Layered silicate clays such as kaolin and montmorillonite (MMT) have been previously shown to induce blood clotting due to their ability to form cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 46 publications
1
34
0
Order By: Relevance
“…Based on these definitions, the present study has designated IC 15 as the cut-off for HSTD. The wound healing promoting properties of MMT are well documented [67]. This has formed the basis for the present assessment of improved would healing effect of our bionanocomposite films.…”
Section: Cytotoxicity Profiles Of the Bionanocomposite Films And Theimentioning
confidence: 77%
See 1 more Smart Citation
“…Based on these definitions, the present study has designated IC 15 as the cut-off for HSTD. The wound healing promoting properties of MMT are well documented [67]. This has formed the basis for the present assessment of improved would healing effect of our bionanocomposite films.…”
Section: Cytotoxicity Profiles Of the Bionanocomposite Films And Theimentioning
confidence: 77%
“…For this purpose, the in vitro scratch assays were performed and the ''wounded'' monolayer BJ cells were treated with the HSTD of the bionanocomposite films for 24 h. Fibroblasts are responsible for most collagen and elastin synthesis as well as organization of the ECM components. The fact that normal human skin fibroblasts (BJ cells) were chosen for the present assay was due to their indispensability in determining how well the wound will ultimately heal [67]. In addition, VEGF, a proangiogenic factor known for its ability in stimulating migration of cultured fibroblasts [68] was used as the positive control.…”
Section: Cytotoxicity Profiles Of the Bionanocomposite Films And Theimentioning
confidence: 99%
“…Similarly, cell adhesion can also be improved by the addition of nanofillers to the composites. Vaiana et al 138 illustrated that addition of hydroxyapatite to poly(vinyl alcohol) hydrogels improved corneal cell adhesion and proliferation. Therefore, these nanocomposites were considered to be a candidate to be used in keratoprosthesis since only poly(vinyl alcohol) hydrogels were able to achieve the mechanical property required for keratoprosthesis but failed in clinical trials for pure cell adhesion.…”
Section: Modification Of Polymeric Nanobiocompositesmentioning
confidence: 99%
“…Growth factors can be designed for therapeutic applications to elicit responses to the ophthalmic materials or selective inhibition or through extrinsic application. 183,200 For this purpose, several types of growth factors, such as fibroblast growth factor, 182,201 epidermal growth factor, 138,202 platelet-derived growth factors, 197,203 and endothelial growth factor 186,187 are used. For instance, Hori et al 202 concluded that the epidermal growth factor along with cationized gelatin hydrogel is an excellent candidate for drug delivery as it has decreased the amount of epithelial defects in rabbits cornea and has facilitated the procedure of wound healing by increasing the epithelial proliferation.…”
Section: Polymer Nanocomposites For Ocular Applicationmentioning
confidence: 99%
“…6,9,14,38 Many efforts have recently been devoted to develop efficient delivery systems for EGF topical application in wound repair. 16,39,40 To facilitate the application, some growth factors were incorporated directly into hydrogel-like formulations, but the active compounds exhibit a rapid release profile from these formulations. 41 Though novel drug delivery systems like microspheres, NPs, and liposomes could prolong the release profile of the proteins, the topical administration of these drug carrier vehicles gave rise to a rapid leakage of the molecules from the wound site.…”
mentioning
confidence: 99%